Abscisic acid enhances cold tolerance in honeybee larvae. Issue 1852 (5th April 2017) - Ramirez, Leonor; Negri, Pedro; Sturla, Laura; Guida, Lucrezia; Vigliarolo, Tiziana; Maggi, Matías; Eguaras, Martín; Zocchi, Elena; Lamattina, Lorenzo
Abstract : The natural composition of nutrients present in food is a key factor determining the immune function and stress responses in the honeybee ( Apis mellifera ). We previously demonstrated that a supplement of abscisic acid (ABA), a natural component of nectar, pollen, and honey, increases honeybee colony survival overwinter. Here we further explored the role of ABA in in vitro -reared larvae exposed to low temperatures. Four-day-old larvae (L4) exposed to 25°C for 3 days showed lower survival rates and delayed development compared to individuals growing at a standard temperature (34°C). Cold-stressed larvae maintained higher levels of ABA for longer than do larvae reared at 34°C, suggesting a biological significance for ABA. Larvae fed with an ABA-supplemented diet completely prevent the low survival rate due to cold stress and accelerate adult emergence. ABA modulates the expression of genes involved in metabolic adjustments and stress responses: Hexamerin 70b, Insulin Receptor Substrate, Vitellogenin, and Heat Shock Proteins 70. AmLANCL2, the honeybee ABA receptor, is also regulated by cold stress and ABA. These results support a role for ABA increasing the tolerance of honeybee larvae to low temperatures through priming effects.